Design enhancement on solar tumble dryer with biomass back-up heater for pepper drying - Ong, Tean Wee (Universiti Malaysia Sarawak (UNIMAS), 2005)
This project is carry out to enhance the performance of existing solar tumble dryer for pepper drying which had been carried out by the previous student from faculty engineering in program mechanical engineering and manufacturing system of University Malaysia Sarawak. The scope of studies and research were concentrated in the continuous drying operation by using biomass heater as a back-up during the poor weather condition and in night time. The effectiveness of adopting this idea into the existing solar tumble dryer will be measured on how fast the fresh pepper can be dried as compare to open drying method. AutoCAD2004 software was used as a drawing tool to design the prototype of biomass back-up heater. The fabrication of prototype for the biomass back-up heater will refer to the requirement of the existing size of the solar tumble dryer in order to carry out the experiment. The biomass back-up heater will be improved step-by-step after each experiment which had carried out. The main concern on the biomass back-up heater was the type of fuel wood used, the requirement of temperature and humidity from the biomass back-up heater. Experiment will also test the whole system of combination of the existing solar tumble dryer and biomass back-up heater regarding on the required temperature and humidity for the whole drying system. Result from the experiment showed biomass back-up heater can shorten the drying time and the process can be carried out in any weather condition.